The Influence of Multimedia Learning Media on the Development of Early Childhood Literacy - Rochmah, Nur (UNIB Press, 2024)
Early childhood education is essential since this is a delicate time, sometimes called the golden age. It is crucial to promote development through literacy throughout this time. This project aims to provide multimedia-based literacy learning to improve child development. The research uses a pre-experimental design and a quantitative technique, utilising the one-group pretest-posttest method with evaluations for both the pretest and posttest in addition to observation. These evaluations yielded data, which were then subjected to descriptive analysis. The study, which involved 15 students from group A at Dharma Wanita Persatuan 1 Kucur Kindergarten, revealed a significant difference between pretest and posttest scores at a significance level below 0.05. Children's conduct changed noticeably before and after participating in multimedia literacy instruction. Six kids showed reading comprehension at first, whereas nine did not. Three of the nine kids struggled with literacy after the intervention, while the other six made progress. This implies that the development of early childhood reading is positively impacted by multimedia learning.